Role of bedrock serpentinization on the development of nickel laterite deposit in Sorowako, Sulawesi, Indonesia - Irfan, U R; Maulana, A.; Muhammad, F (IOP conference series. Earth and environmental science, 2021)
The objective of this research is to analyze the role of bedrock serpentinization on the development of Ni-Laterite deposits in Sorowako, Sulawesi Island, Indonesia. Samples were obtained from coring data in three areas, namely the West Block, East Block, and Petea, which are subject to mineralogical and geochemical analyses. Petrography of the bedrocks was conducted to analyze the mineral composition, texture, and serpentinization degree, and later correlated with the distribution of geochemical elements from X-ray fluorescence method in each laterite zone. The bedrock in the West Block is dunite which consists of predominantly olivine with low degree serpentinization. The bedrock in the East Blocks and Petea consists of peridotite in the form of lherzolite and harzburgite which have been moderate to highly serpentinized. The distribution of elements in each block shows that MgO, SiO 2 , and Ca elements significantly decrease towards the upper laterite profile while Fe, Al, and Cr are enriched in the limonite zone and Ni, Mn, and Co are significantly enriched in the saprolite zone. Ni, Fe, SiO 2 , Cr, MgO, and Mn in the West Block are relatively higher than the East Block and Petea. This study shows that Ni content is relatively higher in West Block compare to East Block and Petea in averages of 1.7%, 1.53%, and 1.3%, respectively. Olivine-rich bedrock and a low degree of serpentinization resulted in high-Ni concentration in the laterite profile, particularly in the saprolite layer. This means that bedrock characteristics and degree of serpentinization were responsible for the development of nickel.